Development and Validation of a Spanish Version of the Grit-S Scale - Arco-Tirado, Jose L.; Fernández-Martín, Francisco D.; Hoyle, Rick H. (Frontiers in Psychology, 2018)
This paper describes the development and initial validation of a Spanish version of the Short Grit (Grit-S) Scale. The Grit‑S Scale was adapted and translated into Spanish using the Translation, Review, Adjudication, Pre-testing and Documentation model and responses to a preliminary set of items from a large sample of university students (N = 1129). The resultant measure was validated using data from a large stratified random sample of young adults (N = 1826). Initial validation involved evaluating the internal consistency of the adapted scale and its subscales and comparing the factor structure of the adapted version to that of the original scale. The results were comparable to results from similar analyses of the English version of the scale. Although the internal consistency of the subscales was low, the internal consistency of the full scale was well within the acceptable range. A two-factor model offered an acceptable account of the data; however, when a single correlated error involving two highly similar items was included, a single factor model fit the data very well. The results support the use of overall scores from the Spanish Grit-S Scale in future research.